Distribution of profits under the companies act 2016: satisfying the insolvency test / Hariati Mansor - Mansor, Hariati (UiTM Cawangan Johor, 2019)
Under the law, distribution of profits or dividends may only be paid to members of a company if there are profits available for that purpose. The Companies Act 2016 requires that the company can only make the distribution to the shareholders out of profit if the company is solvent. Previously, in the Companies Act 1965, the company can pay dividends to its shareholders out of its profits and there is no requirement that the company must fulfill the solvency test. The aim of this paper is to look at the new requirement of solvency test and in what circumstances the company can pay out its dividends. It also examines the effects of non-compliance with the solvency requirements and the implications to the company and directors (if any) under the Act.